Effects of the July 2018 worldwide valsartan recall and shortage on global trends in antihypertensive medication use: a time-series analysis in 83 countries. Issue 1 (27th January 2023) - Choi, Yuna; Santhireswaran, Araniy; Chu, Cherry; Suda, Katie J; Hernandez, Inma; Magnani, Jared W; Tadrous, Mina
Abstract : Objectives: This study aims to examine the effects of the July 2018 worldwide valsartan recall and shortage on global trends of antihypertensive medication use in 83 countries. Methods: A time-series analysis of monthly purchases of valsartan, other angiotensin II receptor blockers (ARBs) and angiotensin-converting enzyme inhibitors (ACEIs) across 83 countries from January 2017 to July 2020 was conducted using the IQVIA MIDAS database. Trends in outcomes were investigated globally and by economic level (developed vs developing economies). The valsartan recall's impact on antihypertensive use was assessed with interventional autoregressive integrated moving average modelling. Results: Global valsartan utilisation trends decreased significantly by 15.7% (−61 166 515 SU; p<0.0001), while global purchases of other ARBs increased by 44.8% (+958 069 420 SU; p=0.8523) and ACEIs increased by 1.6% (+44 106 747 SU; p=0.1102). Of the 32 developed countries, 20 (62.5%) showed a decline in 1-month percentage change in valsartan purchases, whereas only 10 out of 33 developing countries (30.3%) experienced a decrease in valsartan purchases. Mean 1-month, 3-month and 6-month percentage changes for developed countries were −1.2%, −9.3% and −12.2%, respectively, while the changes for developing countries were 25.0%, 7.3% and −1.2%. Conclusions: Global valsartan purchases substantially decreased post-recall, highlighting the far-reaching impacts of drug shortages. Opposing utilisation trends by economic level raise concerns of potential distribution of contaminated medications from developed countries to developing countries. Concerted actions for equitable global access to quality medications and mitigation of drug shortages are needed.